Validity and reliability of an Arabic version of the state-trait anxiety inventory in a Saudi dental setting - Bahammam, Maha A. (Saudi Med J, 2016)
OBJECTIVES: To test the psychometric properties of an adapted Arabic version of the state trait anxiety-form Y (STAI-Y) in Saudi adult dental patients. METHODS: In this cross-sectional study, the published Arabic version of the STAI-Y was evaluated by 2 experienced bilingual professionals for its compatibility with Saudi culture and revised prior to testing. Three hundred and eighty-seven patients attending dental clinics for treatment at the Faculty of Dentistry Hospital, King Abdullah University, Jeddah, Kingdom of Saudi Arabia, participated in the study. The Arabic version of the modified dental anxiety scale (MDAS) and visual analogue scale (VAS) ratings of anxiety were used to assess the concurrent criterion validity. RESULTS: The Arabic version of the STAI-Y had high internal consistency reliability (Cronbach’s alpha: 0.989) for state and trait subscales. Factor analysis indicated unidimensionality of the scale. Correlations between STAI-Y scores and both MDAS and VAS scores indicated strong concurrent criterion validity. Discriminant validity was supported by the findings that higher anxiety levels were present among females as opposed to males, younger individuals as compared to older individuals, and patients who do not visit the dentist unless they have a need as opposed to more frequent visitors to the dental office. CONCLUSION: The Arabic version of the STAI-Y has an adequate internal consistency reliability, generally similar to that reported in the international literature, suggesting it is appropriate for assessing dental anxiety in Arabic speaking populations.